Pemberdayaan Santri Berbasis Kewirausahaan di Pondok Pesantren Putri Yatama Mandiri Ditinjau dari Perspektif Ekonomi Islam - Azis, Muh Sofyan; Khalid, Idham; Wahyuni, Sri (Robust: Research of Business and Economics Studies, 2025)
This study aims to explore the application of entrepreneurship-based student empowerment at the Yatama Mandiri Putri Islamic Boarding School from an Islamic economic perspective. This research is a field research with a qualitative approach that aims to understand the empowerment process through business units such as Islamic boarding school cooperatives, bread and donut production, and tilapia cultivation. Data collection techniques are carried out through interviews, observations, and documentation involving pesantren administrators, business assistants, and students who are actively involved. The results of the study show that pesantren integrates Islamic values and entrepreneurship training directly, providing real experience for students in managing a business and encouraging financial independence. From an Islamic economic perspective, this empowerment emphasizes the principles of justice, social responsibility, and business ethics. This research contributes to the development of science in the field of Islamic education and entrepreneurship, and shows how pesantren can function as an agent of economic empowerment and community development.